Happiness, hope, and affection as predictors of quality of life and functionality of individuals with heart failure at three-month follow-up - Leal, Elisabete Nave (2013)
The scientific evidence supporting the management of the chronically ill in a positive psychological perspective in opposition to traditional pathological approach is scarce. This study examines issues associated with recovery of health status in heart failure, in particular hope, affection, and happiness. We use a longitudinal study of 128 symptomatic patients who after medical intervention reported improved quality of life and function at 3-month follow-up. We evaluated the contribution of happiness, hope and affection, individually and as a whole, in the quality of life and functionality of individuals with heart failure. Happiness (Subjective Happiness Scale), Hope (HOPE Scale), and affection (PANAS (positive and negative affect schedule)) were determined before medical intervention. Individually, we found that happiness is correlated with the quality of life and functionality, hope to self-efficacy dimension of the quality of life scale, positive affect to functionality and negative affect with symptoms dimension, quality of life dimension, and overall sum of the quality of life scale. Overall, we found that happiness has a unique contribution to the quality of life, except in self-efficacy dimension where hope takes this contribution and positive affect has a unique contribution to the functionality in this short-term follow-up. The results highlight the importance of positive variables to health outcomes for people with heart failure and should be considered in intervention programs for this syndrome.